The Effectiveness of Bibliotherapy in Reducing Body Image Dissatisfaction Among High School Girls - Sukamto, Monique Elizabeth (Faculty of Psychology, Universitas Surabaya, 2008)
The aim of this study is to evaluate the effectiveness of bibliotherapy in reducing body im- age dissatisfaction among high school girls. Participants were 45 girls from three different high schools, whose BMI were normal (18.5 – 22.9) and experienced moderate to very high body image dissatisfaction. Using pretest – posttest control group design, participants from each high school were assigned to one of three conditions: interactive or reading bibliotherapy as experimental conditions or as waiting-list control group. Body image dissatisfaction of each participant was measured at pre- treatment, post-treatment, and 1-month follow-up and analyzed using One-Way ANOVA and General Linear Model – Univariate. The result of this study showed that either interactive (sig.= 0.000 < 0.05) or reading bibliotherapy (sig.= 0.012 < 0.05) was effective in reducing body image dissatisfaction among high school girls and their effectiveness were maintained until 1-month follow-up. Penelitian ini dilakukan untuk mengetahui efektivitas bibliotherapy dalam mengurangi ket- idakpuasan terhadap citra tubuh pada siswi SMU. Subjek penelitian ini adalah 45 siswi SMU dari tiga SMU yang terpisah, yang memiliki IMT yang tergolong normal (18.5 – 22.9) dan mengalami keti- dakpuasan terhadap citra tubuh yang tergolong cukup hingga sangat tinggi. Menggunakan pretest – posttest control group design, para subjek dibagi dalam tiga kelompok, yaitu interactive bibliother- apy, reading bibliotherapy, dan kelompok kontrol (waiting-list control group). Pengukuran dilak- sanakan sebanyak tiga kali, yaitu pada saat sebelum perlakuan, setelah perlakuan, dan sebulan setelah perlakuan serta dianalisis menggunakan Analisis Varian Satu Arah dan Analisis Varian Sampel Ber- korelasi. Hasil penelitian ini menunjukkan bahwa baik interactive (sig.= 0.000 < 0.05) maupun read- ing bibliotherapy (sig.= 0.012 < 0.05) terbukti efektif dalam mengurangi ketidakpuasan terhadap citra tubuh pada siswi SMU dan efektivitasnya dapat tetap bertahan hingga satu bulan setelah perlakuan.